Coated gallium nitride substrate, gallium nitride / diamond bonded structure, and methods of making same
Patent Information
- Application Number
- CN202611408447.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-16
AI Technical Summary
[0009]传统的空间异质结构往往依赖于几何形貌的物理起伏或厚度设计,该类方案虽能增加局部接触面积,但其非连续、非共面的宏观特征直接破坏了全晶圆键合所必需的平滑表面;在大面积晶圆键合实践中,这种物理厚度差异不可避免地会诱发大面积的未键合空洞与接触失效
本发明的一种镀膜氮化镓基板或一种氮化镓/金刚石键合结构的镀膜层(即中间层)通过在径向平面内构筑阶梯式演变的组分分布,自中心向外围按特定配比进行逐级调控,在正投影覆盖器件核心发热源的键合结构的中心区域,采用纯SiC刚性高导热相,以保障近结区的极限散热效率;自中心向外围推进时,设置组分过渡阶梯,实现镀膜层物相与物理特性的台阶式渐变;而在几何缺陷(TTV、Warp)最严重且剪切与剥离应力达到峰值的最外围区域,则完全过渡为纯Si的低模量顺应相,利用外围边缘Si的化学活性与低模量的特性,通过在微观尺度构建强共价桥接以弥合形貌缺陷,并在宏观尺度构筑平缓的热膨胀系数梯度以耗散应变能,补偿了单晶金刚石由于TTV和Warp造成的微观间隙,从而显著降低氮化镓与金刚石间未键合空洞率,避免氮化镓与金刚石间接触失效。
Smart Images

Figure CN122935248A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor technology, and more specifically, relates to coated gallium nitride substrates, gallium nitride / diamond bonding structures, and their preparation methods. Background Technology
[0002] As electronic devices evolve towards higher frequencies, higher power, and higher integration, the thermal management of semiconductor materials faces unprecedented challenges. In the fields of power electronics and high-frequency microwave devices, gallium nitride (GaN) exhibits enormous application potential due to its excellent intrinsic physical properties, such as a wide bandgap, high breakdown electric field, and high saturation electron velocity. However, limited by severe self-heating effects under high-power operation, the actual power density of GaN-based devices typically only reaches one-quarter of the theoretical limit. The core issue lies in the rapid accumulation and inefficient dissipation of heat in the channel region. The silicon (Si) or silicon carbide (SiC) substrates used in traditional fabrication, due to their limited thermal conductivity, can no longer meet the heat dissipation requirements of next-generation devices, leading to severe performance degradation and limiting their application range. Therefore, overcoming the thermal management bottleneck of GaN devices has become crucial to unlocking their potential performance and promoting their industrial application.
[0003] Diamond, possessing ultra-high thermal conductivity, extremely low coefficient of thermal expansion, high resistivity, and excellent chemical stability, is considered an ideal next-generation substrate material for high-power electronic devices. Heterogeneous integration of diamond and GaN can significantly enhance the heat dissipation efficiency of devices and reduce channel peak temperatures, thereby greatly improving device reliability and performance. Currently, diamond-GaN integration strategies mainly fall into three categories: epitaxial growth of GaN on diamond substrates, direct deposition of diamond on GaN heterostructures, and diamond / GaN bonding. The first two "direct growth" methods are limited by severe lattice mismatch and differences in thermal expansion coefficients between materials, and the high-temperature fabrication process easily induces thermal stress defects such as epitaxial layer warping and cracking, restricting their large-scale mass production applications. In contrast, low-temperature / room-temperature bonding technology of diamond and GaN can effectively avoid the aforementioned welding defects, becoming the most feasible and promising high-efficiency heat dissipation solution.
[0004] At present, single-crystal or polycrystalline diamonds, during chemical vapor deposition growth and subsequent machining, are subject to the dual effects of anisotropic growth rates and extremely high intrinsic residual stress, resulting in significant total thickness variation (TTV) and warp. This geometric non-uniformity spanning micro and macro dimensions leads to a non-linear degradation of the diamond's flatness in the radial plane; especially in the edge regions, the morphological deviations and gap undulations induced by TTV and warp reach a cumulative peak. The superposition of this macro- and micro-geometric defect directly deteriorates the contact quality of subsequent bonding interfaces.
[0005] In diamond and GaN bonding techniques, introducing an intermediate layer (Si, SiO2, SiC) is a conventional approach to circumvent lattice mismatch and thermal stress during high-temperature epitaxial growth. However, existing bonding schemes all face the bottleneck of failing to achieve both "high bonding quality" and "excellent thermal / electrical properties".
[0006] If a low-modulus compliant interlayer such as Si is used, it readily forms highly active dangling bonds under room-temperature vacuum activation, significantly reducing the bonding energy barrier and constructing a dense covalent bridging network. This compliance not only bridges the morphological gaps caused by TTV and warpage at the microscale, but its moderate coefficient of thermal expansion also buffers thermal mismatch stress at the macroscale. However, the fatal flaw is that the low thermal conductivity of the silicon layer severely blocks the vertical heat dissipation path directly below the heat-generating area, greatly diminishing the thermal conductivity advantage of diamond. Conversely, if a homogeneous rigid interlayer such as SiC is used, although it possesses high thermal conductivity, its extremely high Young's modulus limits the film's ability to locally adapt to deformation under axial pressure, failing to compensate for edge geometric gaps. This inevitably leads to a large number of microscopic unbonded voids and contact failures remaining in the edge regions.
[0007] In addition, although metal interlayer (such as Au, Ag, Mo, Cu) bonding can achieve high-strength connection by taking advantage of the ductility of metal, its high conductivity will introduce serious parasitic capacitance to high-frequency devices such as GaN HEMT (HEMT is a high electron mobility transistor), resulting in degraded radio frequency performance; and under high power operation, the interface is prone to electromigration failure, and thermal stress problems cannot be eliminated.
[0008] On the other hand, while direct bonding between diamond and GaN theoretically does not introduce additional thermal resistance, the process conditions are demanding (requiring maintenance of 10... -7 (Ultra-high vacuum at the Pa level) and the tendency to form an amorphous graphitized transition layer at the interface, leading to a significant increase in interfacial thermal resistance. More seriously, traditional direct bonding often uses homogeneous planar contacts, lacking stress relief mechanisms. As the size of full-wafer-level heterogeneous integration increases, during subsequent high-temperature annealing or cyclic service, the mismatch in thermal expansion coefficients between materials, combined with residual macroscopic non-uniform internal stress from processing, will induce strong non-uniform shear and peeling stresses at the wafer edges. This composite stress concentration, lacking localized buffering and control, easily leads to interfacial microcracks, localized voids, or even overall peeling, seriously threatening the long-term reliability and heat dissipation sustainability of the device.
[0009] Traditional spatial heterogeneous structures often rely on physical undulations in geometry or thickness design. While such solutions can increase local contact area, their discontinuous and non-coplanar macroscopic characteristics directly disrupt the smooth surface necessary for full-wafer bonding. In large-area wafer bonding practices, this physical thickness difference inevitably induces large areas of unbonded voids and contact failures. Therefore, to overcome the dual mechanical and thermal bottlenecks of traditional rigid homogeneous planar bonding layers, it is particularly urgent to develop a gallium nitride / diamond bonding structure with a novel intermediate layer that combines "globally high coplanar flatness" and a "global stress relief mechanism." Summary of the Invention
[0010] The purpose of this invention is to provide a coated gallium nitride substrate, a gallium nitride / diamond bonding structure, and a method for fabricating the same. The gallium nitride / diamond bonding structure of this invention constructs a novel intermediate layer with globally coplanar smoothness on the surface and radial "central rigidity-edge compliance" gradient functional composite characteristics inside, so as to simultaneously achieve "efficient thermal conduction in the central region" and "localized adaptation to stress / thermal mismatch in the edge region", thereby avoiding the induction of large-area unbonded voids and contact failures between gallium nitride and diamond.
[0011] To achieve the above objectives, a first aspect of the present invention provides a coated gallium nitride substrate, comprising a GaN epitaxial wafer and a coating layer deposited on the GaN epitaxial wafer. The phase composition ratio of the coating layer is distributed in a stepped gradient along the radial direction. The phase composition at the center of the coating layer is pure SiC, the phase composition at the outermost edge of the coating layer is pure Si, and the phase composition of the transition region between the center of the coating layer and the outermost edge of the coating layer is a mixed phase of SiC and Si. From the center to the outermost edge, the proportion of Si in the transition region increases stepwise.
[0012] Furthermore, the initial surface roughness Ra of the GaN epitaxial wafer is less than 5 nm.
[0013] Furthermore, the phase composition at the center of the coating layer is pure 3C-SiC, 4H-SiC, or 6H-SiC.
[0014] Furthermore, the thickness of the coating layer is 10~30 nm.
[0015] Furthermore, the original substrate of the GaN epitaxial wafer is sapphire.
[0016] In a second aspect, the present invention provides a gallium nitride / diamond bonding structure comprising the above-described coated gallium nitride substrate and a single crystal diamond, wherein the single crystal diamond is bonded to the coating layer.
[0017] Furthermore, the initial surface roughness Ra of the single-crystal diamond is less than 10 nm.
[0018] A third aspect of the present invention provides a method for preparing a coated gallium nitride substrate, comprising the following steps: (1) The GaN epitaxial wafer is subjected to ultra-clean cleaning pretreatment to remove surface impurities; (2) A coating layer is deposited on the surface of the pretreated GaN epitaxial wafer using photolithography and patterning overlay processes to obtain the coated gallium nitride substrate. The phase composition ratio of the coating layer is distributed in a stepped gradient along the radial direction. The phase composition at the center of the coating layer is pure SiC, the phase composition at the outermost edge of the coating layer is pure Si, and the phase composition in the transition region between the center of the coating layer and the outermost edge of the coating layer is a mixed phase of SiC and Si. From the center to the outermost edge, the proportion of Si in the transition region increases stepwise.
[0019] A fourth aspect of the present invention provides a method for preparing a gallium nitride / diamond bonding structure, comprising the following steps: (1) Perform ultra-clean cleaning pretreatment on single crystal diamond and GaN epitaxial wafers to remove surface impurities; (2) A coating layer is deposited on the surface of the pretreated GaN epitaxial wafer using photolithography and patterning overlay processes. The phase composition ratio of the coating layer is distributed in a stepped gradient along the radial direction. The phase composition at the center of the coating layer is pure SiC, the phase composition at the outermost edge of the coating layer is pure Si, and the phase composition of the transition region between the center of the coating layer and the outermost edge of the coating layer is a mixed phase of SiC and Si. From the center to the outermost edge, the proportion of Si in the transition region increases stepwise. (3) The GaN epitaxial wafer after the deposition of the coating layer is chemically cleaned and dried to remove the natural oxide layer and surface impurities; (4) The pretreated single crystal diamond and the bonding surface of the coating layer are activated, and then directly bonded to obtain the gallium nitride / diamond bonding structure.
[0020] The phase composition ratio of the gallium nitride / diamond bonded structure coating layer (i.e., the intermediate layer) of this invention exhibits a continuous physical property gradient distribution from the center to the outer edge in the radial plane, including a thermally conductive rigid central region that orthogonally covers the core heat source of the device and a low-modulus compliant region extending to the edge. This ensures near-junction-limited heat dissipation in the central region while effectively mitigating the non-uniform shear stress and peel stress induced by thermal expansion coefficient mismatch using the low-modulus compliant phase in the peripheral edge region.
[0021] Furthermore, the initial surface roughness Ra of the single-crystal diamond is less than 10 nm, and the initial surface roughness Ra of the GaN epitaxial wafer is less than 5 nm. The quality of room-temperature surface-activated bonding is highly dependent on the microscopic smoothness of the interface. If the roughness is too large, surface peaks and valleys will hinder atomic-level contact and easily induce microscopic unbonded voids. Considering the extremely high hardness and processing cost of single-crystal diamond, limiting its Ra to less than 10 nm is the optimal balance between mass production limits and bonding quality; while the GaN epitaxial wafer processing technology is mature, limiting its Ra to less than 5 nm can provide a contact reference surface with extremely high smoothness.
[0022] Furthermore, the phase composition at the center of the coating layer is pure 3C-SiC, 4H-SiC, or 6H-SiC; preferably pure 3C-SiC or 4H-SiC, which has higher thermal conductivity.
[0023] Furthermore, the thickness of the coating layer is 10~30 nm. This ensures that the coating layer maintains high continuity and local plastic deformation compensation capability after ion bombardment loss, while controlling the interface thermal resistance and stress at an extremely low level. 10~30 nm is the optimal size range for achieving room temperature bonding of high-performance heterogeneous integrated wafers.
[0024] Furthermore, it also includes step (5): peeling off the original substrate of the GaN epitaxial wafer.
[0025] Further, in step (2), the deposition of the coating layer is carried out using a multi-target co-sputtering system with a first cathode target and a second cathode target. The first cathode target is equipped with a high thermal conductivity target SiC, and the second cathode target is equipped with a low modulus target Si.
[0026] Further, in step (2), the photolithography development and patterning overlay process specifically involves: coating the pretreated GaN epitaxial wafer surface with photoresist and pre-baking it; using a concentric ring mask for exposure and development to expose the concentric ring feature region at a specific location; then moving it into a multi-target co-sputtering chamber; and precisely controlling the sputtering power ratio of the high thermal conductivity target and the low modulus target according to the radial position of the feature region to deposit a phase film of constant thickness; then immersing it in a stripping solvent and using ultrasonic stripping to remove excess photoresist and non-target area film. Ultimately, this results in a precise decrease in the 3C-SiC or 4H-SiC content and a precise increase in the pure Si content in each concentric ring transition region extending from the central high thermal conductivity rigid region outwards, until the outermost edge region completely transitions to pure Si. The concentric ring can be a concentric square ring or a concentric circular ring.
[0027] Further, in step (4), the activation process is as follows: under ultra-high vacuum conditions, a high-energy fast atom beam or a high-pressure plasma beam is used to bombard the surface to be bonded, wherein the ultra-high vacuum pressure reaches 10 -7 Pa level.
[0028] Furthermore, in step (4), a high-energy Ar atom beam is used to bombard the surface to be bonded, with the beam energy set to 1.0~1.5 keV and the ion beam density set to 30~50 μA / cm. 2 .
[0029] Furthermore, in step (4), after the activated surfaces come into contact with each other, a uniform axial pressure is applied to the heterogeneous structure by a mechanical indenter to complete the room temperature bonding.
[0030] Furthermore, in step (3), the chemical cleaning uses hydrofluoric acid cleaning solution or a mixture of hydrochloric acid and hydrogen peroxide cleaning solution.
[0031] Further, in step (1), the pretreatment is as follows: first, the single crystal diamond and the GaN epitaxial wafer are subjected to multi-stage ultrasonic cleaning in sequence using acetone, anhydrous ethanol and deionized water; then, the single crystal diamond is cleaned with an alkaline solution, wherein the alkaline solution is a mixed solution of ammonia and hydrogen peroxide, or a mixed solution of sodium hydroxide and hydrogen peroxide.
[0032] Further, in step (5), the original substrate of the GaN epitaxial wafer is peeled off using a laser separation method.
[0033] Compared with the prior art, the present invention has the following technical effects: The present invention discloses a gallium nitride substrate or a gallium nitride / diamond bonded structure with a coated layer (i.e., an intermediate layer). This is achieved by constructing a stepped composition distribution in the radial plane, with gradual control from the center outwards according to a specific ratio. In the central region of the bonded structure, which covers the core heat source of the device in its orthogonal projection, a pure SiC rigid high thermal conductivity phase is used to ensure the ultimate heat dissipation efficiency near the junction region. As the composition transitions from the center outwards, a step transition ladder is set to achieve a gradual change in the phase and physical properties of the coated layer. Meanwhile, in the geometric defects (TTV)... In the outermost region where the shear and peel stresses (TTV and Warp) are most severe and reach their peak, the phase completely transitions to a low-modulus compliant phase of pure Si. By utilizing the chemical reactivity and low modulus of Si at the outer edge, strong covalent bridging is constructed at the microscale to bridge morphological defects, and a gentle thermal expansion coefficient gradient is constructed at the macroscale to dissipate strain energy. This compensates for the microscopic gaps caused by TTV and Warp in single-crystal diamond, thereby significantly reducing the unbonded void ratio between gallium nitride and diamond and avoiding contact failure between gallium nitride and diamond.
[0034] The present invention discloses a method for fabricating a coated gallium nitride substrate or a method for fabricating a gallium nitride / diamond bonded structure. By introducing high-precision photolithography and patterning overlay processes, a coating layer with a radially varying step-type composition gradient is constructed. This achieves good spatial decoupling of thermal and mechanical properties. In the central region of the bonded structure, which covers the core heat source of the device in orthogonal projection, high thermal conductivity pure SiC is retained to ensure high heat dissipation near the junction. In the outermost edge region, where geometric defects are most severe, it completely transitions to a pure Si layer. Utilizing the chemical reactivity and low modulus of the outer edge Si, strong covalent bridging is constructed at the microscale to bridge morphological defects, and a gentle thermal expansion coefficient gradient is constructed at the macroscale to dissipate strain energy. This compensates for the microscopic gaps caused by TTV and Warp in single-crystal diamond, thereby significantly reducing the unbonded void ratio between gallium nitride and diamond and avoiding contact failure between gallium nitride and diamond.
[0035] The unique radial stepped composition architecture coating layer of this invention can not only accurately adapt to the macroscopic morphological defects at the edge of the gallium nitride / diamond bonding structure and release thermal mismatch stress, but also ensure that the heat directly below the core heat generation area is rapidly conducted to the diamond substrate, opening up a new path for the industrial mass production of large-size, high-reliability, high-power GaN / diamond heterostructure integrated wafers. Attached Figure Description
[0036] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0037] Figure 1 This is a schematic diagram of the structure of the GaN epitaxial wafer provided in Embodiment 1 of the present invention; Figure 2 This is a schematic diagram of the structure of the GaN epitaxial wafer with a coating layer provided in Embodiment 1 of the present invention; Figure 3 for Figure 2 A top-view structural diagram; Figure 4 This is a schematic diagram of the gallium nitride / diamond bonding structure provided in Embodiment 1 of the present invention before the removal of the original substrate; Figure 5 for Figure 4 A schematic diagram of the structure after removing the original substrate; Figure 6 This is a scanning acoustic microscope image of the gallium nitride / diamond bonding structure provided in Embodiment 1 of the present invention; Figure 7This is a scanning acoustic microscope image of the gallium nitride / diamond bonding structure provided in Embodiment 2 of the present invention; Figure 8 This is a scanning acoustic microscope image of the gallium nitride / diamond bonding structure provided in Comparative Example 1 of the present invention; Figure 9 This is a scanning acoustic microscope image of the gallium nitride / diamond bonding structure provided in Comparative Example 2 of the present invention.
[0038] The following are the labeling elements in the figure: 1. Original substrate, 2. GaN epitaxial wafer, 3. Coating layer, 4. Diamond. Detailed Implementation
[0039] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0040] In this invention, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0041] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0042] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of embodiments of the invention, "first" may also be referred to as "second," and similarly, "second" may also be referred to as "first." Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature.
[0043] The following embodiments use the bonding of a square GaN epitaxial wafer and a square single-crystal diamond substrate as an example, but the shape of the GaN epitaxial wafer and the single-crystal diamond substrate is not limited to square, for example, it can also be circular.
[0044] Unless otherwise specified, the "%" mentioned in the following intermediate layer refers to the relative molar proportions of silicon carbide (SiC) and elemental silicon (Si) in the total components of the intermediate layer within the corresponding region.
[0045] Example 1
[0046] This invention provides a GaN / diamond bonding structure using 3C-SiC and Si as intermediate layers and its preparation method, as detailed below: Step 1, ultra-clean sample pretreatment: Provide sapphire-based GaN epitaxial wafers 2 (structure as follows) Figure 1 As shown, it has a raw substrate 1 (sapphire with a surface roughness Ra < 5 nm) and a single-crystal diamond 4 of the same size (surface roughness Ra < 10 nm). The GaN epitaxial wafer 2 and the single-crystal diamond 4 were sequentially immersed in high-purity acetone, high-purity anhydrous ethanol, and deionized water, and ultrasonically cleaned continuously for 8 minutes each at room temperature to remove trace amounts of organic residues and foreign particles adsorbed on the surface. Then, the surface of the GaN epitaxial wafer 2 was completely dried using a high-purity nitrogen gas flow.
[0047] The single-crystal diamond 4 was immersed in a pre-prepared alkaline cleaning solution. This alkaline solution was prepared by mixing 10% high-purity NaOH solution, 30% H2O2, and deionized water in a volume ratio of 1:1:4. The solution was heated to 65 °C and continuously immersed for 10-15 minutes to completely remove impurities from the surface of the single-crystal diamond.
[0048] The second step is the patterning and deposition of the gradient radially varying coating layer (i.e., the intermediate layer): Using photolithography and patterning overlay processes, a concentric square annular intermediate layer with a relatively constant total thickness and a radially gradient distribution of phase composition is deposited on the pretreated sapphire-based GaN epitaxial wafer. In the central region of the intermediate layer, which projectively covers the core heat source of the device, the phase composition is 100% pure 3C-SiC. The concentric square annular region extending outwards from the high thermal conductivity rigidity central region has a mixed phase composition of 3C-SiC and Si, with the proportion of pure Si increasing stepwise from the inside out. The concentric square annular region extending to the outermost edge has a phase composition of 100% pure Si. Details are as follows: 1) Fabrication of the central high thermal conductivity rigid region: Photoresist was uniformly spin-coated onto the surface of the dried GaN epitaxial wafer 2. A centrally square transparent mask was used for exposure and development, exposing only the central square region that positively projects over the core heat source of the device. The GaN epitaxial wafer 2 was then placed into the ultra-high vacuum deposition chamber of a multi-target magnetron sputtering system (with the base vacuum level evacuated to 2.0 × 10⁻⁶). -5 High-purity argon gas was introduced at a flow rate of 20–40 sccm, and the working pressure was maintained at 0.5 Pa. Before deposition, the radio frequency assisted ion beam source was turned on, and the low ion bombardment energy was set to 200–500 eV, and the ion beam current density was set to 20–50 μA / cm.2 The exposed area was bombarded in situ for 1-2 minutes to remove the natural oxide layer and expose the unsaturated dangling bonds on the GaN surface. Then, the 3C-SiC target was activated, and the sputtering power was set to 400 W to deposit a high thermal conductivity 3C-SiC film with a strictly controlled thickness of 20 nm in the central region. The GaN epitaxial wafer 2 was then removed and immersed in a stripping solution for ultrasonic removal of excess resist, completing the preparation of the central region.
[0049] 2) Fabrication of multi-level stepped transition regions: Concentric square annular masks with different inner and outer diameters are used. A cyclic process of "photolithography overlay - exposure and development - in-situ activation - co-sputtering deposition - stripping of residual resist" is performed sequentially from the inside out. The overlay precision is controlled at the sub-micron level to eliminate boundary protrusions. Compared to the previous level, the phase composition ratio of each concentric square ring decreases by 10% in 3C-SiC content while increasing by 10% in Si content. Specific operations are as follows: a. Perform a second round of photolithography to expose the first-level concentric square rings adjacent to the central region. After placing it in the sputtering chamber and activating it in situ under the same low-energy conditions, simultaneously turn on the 3C-SiC target and the Si target. Based on the pre-calibrated deposition rate, precisely adjust the co-sputtering power ratio (set the 3C-SiC target power to 360 W and the Si target power to 40 W) to deposit a 20 nm thick mixed-phase film with a composition of 90% 3C-SiC and 10% Si. Then, peel off the remaining resist.
[0050] b. Next, a third round of photolithography was performed to expose the outermost second-level concentric square rings. The dual target power ratio was adjusted again (3C-SiC target power was set to 320 W, and Si target power to 80 W), and a mixed-phase film with a thickness of 20 nm and a composition of 80% 3C-SiC and 20% Si was deposited. Then, the remaining resist was peeled off.
[0051] c. Following this pattern, by cyclically adjusting the dual-target sputtering power, concentric square rings with gradient compositions of 70% 3C-SiC + 30% Si, 60% 3C-SiC + 40% Si are constructed sequentially until the outermost transition ring reaches a mixed phase of 10% 3C-SiC and 90% Si. The deposition thickness of all transition ring films is strictly maintained at 20 nm to ensure the global coplanar flatness of the GaN epitaxial wafer.
[0052] 3) Preparation of the low-modulus compliant edge region: A final round of photolithography spin coating was performed, using a mask with a concentric square ring for light transmission to expose the annular edge region extending to the outermost edge of the GaN epitaxial wafer 2. After in-situ activation in the sputtering chamber, the 3C-SiC target was completely shut off, with only the Si target turned on and the sputtering power set to 350 W, depositing a 20 nm thick 100% pure Si film. After stripping off the excess resist, a radial gradient intermediate layer (layer 3) with a constant total thickness of 20 nm was formed on the surface of the GaN epitaxial wafer 2. This intermediate layer exhibits a multi-level stepwise change in phase composition from the center outwards. The resulting GaN epitaxial wafer with the intermediate layer is shown below. Figure 2 As shown, Figure 3 for Figure 2 A top-view structural diagram.
[0053] The third step is to remove the natural oxides in the intermediate layer: A GaN epitaxial wafer with a radially varying compositional gradient intermediate layer was placed in a dilute hydrofluoric acid cleaning solution at room temperature. This cleaning solution was prepared by diluting 50% concentrated hydrofluoric acid with deionized water at a volume ratio of 1:20. The GaN epitaxial wafer was completely immersed in the dilute acid solution and allowed to stand for 2–5 minutes to allow the dilute hydrofluoric acid to thoroughly dissolve the natural oxide layer and surface impurities, while ensuring that the intrinsic morphology of the material is not damaged.
[0054] After the chemical treatment is completed, the pretreated single-crystal diamond 4 and the chemically cleaned GaN epitaxial wafer 2 are quickly transferred into an ultrapure water bath and continuously rinsed for 6-8 minutes at a flow rate of 8-10 L / min. After rinsing, they are transferred into a high-vacuum spin dryer and spun dry at a high speed of 3000-3500 rpm for 2-3 minutes under a 60 °C environment with 99.9% pure hot nitrogen gas.
[0055] Step 4: Ultra-high vacuum surface activation and room temperature bonding: After spin drying, the GaN epitaxial wafer 2 with a gradient radially varying coating layer 3 and the single-crystal diamond 4 are simultaneously fed into an ultra-high vacuum surface activation and bonding chamber. When the chamber's base vacuum is evacuated to 5.0 × 10⁻⁶... -7 At Pa, the surfaces to be bonded, the coated layer 3 and the single-crystal diamond 4, were simultaneously bombarded with a high-energy Ar atomic beam for 1 min. The beam energy was set to 1.0~1.5 keV, and the ion beam current density was set to 30~50 μA / cm. 2 Immediately after bombardment, the beam was shut off. While maintaining the cavity at room temperature, the coated layer 3 and the activated surface of the single-crystal diamond 4 were precisely aligned and bonded, and a uniformly distributed axial mechanical pressure of 2.0 MPa was directly applied. This mechanical pressure was maintained for 10–15 minutes, ultimately achieving bonding. The resulting GaN / diamond bonded structure is shown below.Figure 4 As shown.
[0056] Step 5, removal of the original substrate: The sapphire substrate 1 was peeled off and removed from the bonded heterostructure using a laser lift-off process, ultimately obtaining a high-quality target GaN / diamond heterostructure (i.e., GaN / diamond bonded structure), such as... Figure 5 As shown.
[0057] Step 6, Bonding quality inspection: The cleaned GaN / diamond integrated wafer was dried with high-purity argon gas and placed under a scanning acoustic microscope for non-destructive testing of the void ratio at the bonding interface. The test results show that the GaN / diamond integrated wafer prepared in this embodiment has an interface void ratio of only 8.32% (test results are shown in the figure). Figure 6 (As shown).
[0058] Example 2
[0059] This embodiment provides a GaN / diamond bonded structure using 4H-SiC and Si as intermediate layers and its preparation method, as detailed below: Step 1, ultra-clean sample pretreatment: Sapphire-based GaN epitaxial wafers (surface roughness Ra < 5 nm) and single-crystal diamond of the same size (surface roughness Ra < 10 nm) are provided. The GaN epitaxial wafer and single-crystal diamond are sequentially immersed in high-purity acetone, high-purity anhydrous ethanol, and deionized water, and ultrasonically cleaned continuously for 8 min each at room temperature to remove trace organic residues and foreign particles adsorbed on the surface. Then, the surface of the GaN epitaxial wafer is completely dried using a high-purity nitrogen gas flow.
[0060] The single-crystal diamond was immersed in a pre-prepared alkaline cleaning solution. This alkaline solution was prepared by mixing 30% ammonia, 30% H2O2, and deionized water in a volume ratio of 1:1:4. The solution was heated to 60 °C and continuously immersed for 10–15 min.
[0061] The second step is the patterning and deposition of the gradient radially varying intermediate layer: Using photolithography and patterning overlay processes, a concentric square annular intermediate layer with a relatively constant total thickness and a radially gradient distribution of phase composition is deposited on the pre-treated sapphire-based GaN epitaxial wafer. In the central region of the intermediate layer, which projectively covers the core heat source of the device, the phase composition is 100% pure 4H-SiC. The concentric square annular region extending outwards from the high thermal conductivity rigidity central region has a mixed phase composition of 4H-SiC and Si, with the proportion of pure Si increasing stepwise from the inside out. The concentric square annular region extending to the outermost edge has a phase composition of 100% pure Si. Details are as follows: 1) Fabrication of the central high thermal conductivity rigid region: Photoresist is uniformly spin-coated onto the surface of the dried GaN epitaxial wafer. A centrally square transparent mask is used for exposure and development, exposing only the central square region that orthogonally covers the core heat source of the device. The GaN epitaxial wafer is then placed into the ultra-high vacuum deposition chamber of a multi-target magnetron sputtering system (with the base vacuum level evacuated to 3.0 × 10⁻⁶). -5 High-purity argon gas was introduced at a flow rate of 30-50 sccm, and the working pressure was maintained at 0.5 Pa. Before deposition, the radio frequency assisted ion beam source was turned on, and the low ion bombardment energy was set to 300-600 eV, and the ion beam current density was 40-60 μA / cm. 2 The exposed area was bombarded in situ for 2-3 minutes to remove the natural oxide layer and expose the unsaturated dangling bonds on the GaN surface. Then, a 4H-SiC target was activated, and the sputtering power was set to 400 W to deposit a high thermal conductivity 4H-SiC film with a strictly controlled thickness of 20 nm in the central region. The GaN epitaxial wafer was then removed and immersed in a stripping solution for ultrasonic removal of excess resist, completing the preparation of the central region.
[0062] 2) Fabrication of multi-level stepped transition regions: Concentric square annular masks with different inner and outer diameters are used. A cyclic process of "photolithography overlay - exposure and development - in-situ activation - co-sputtering deposition - stripping of residual resist" is performed sequentially from the inside out. The overlay precision is controlled at the sub-micron level to eliminate boundary protrusions. Compared to the previous level, the phase composition ratio of each concentric square ring decreases by 10% in 4H-SiC content while increasing by 10% in Si content. Specific operations are as follows: a. Perform a second round of photolithography to expose the first-level concentric square rings adjacent to the central region. After placing it in the sputtering chamber and activating it in situ under the same low-energy conditions, simultaneously activate the 4H-SiC target and the Si target. Based on the pre-calibrated deposition rate, precisely adjust the co-sputtering power ratio (set the 4H-SiC target power to 360 W and the Si target power to 40 W) to deposit a 20 nm thick mixed-phase film with a composition of 90% 4H-SiC and 10% Si. Then, peel off the remaining resist.
[0063] b. Next, a third round of photolithography was performed to expose the outermost second-order concentric square rings. The dual-target power ratio was adjusted again (the 4H-SiC target power was set to 320 W and the Si target power to 80 W), and a mixed-phase film with a thickness of 20 nm and a composition of 80% 4H-SiC and 20% Si was deposited. Then, the remaining resist was peeled off.
[0064] c. Following this pattern, by cyclically adjusting the dual-target sputtering power, concentric square rings with gradient compositions of 70% 4H-SiC + 30% Si, 60% 4H-SiC + 40% Si are constructed sequentially until the outermost transition ring reaches a mixed phase of 10% 4H-SiC and 90% Si. The deposition thickness of all transition ring films is strictly maintained at 20 nm to ensure the global coplanar flatness of the GaN epitaxial wafer.
[0065] 3) Preparation of the low-modulus compliant edge region: A final spin-coating process was performed using a photolithography mask with a concentric square ring for exposure and development, revealing the annular edge region extending to the outermost edge of the GaN epitaxial wafer. After in-situ activation in the sputtering chamber, the 4H-SiC target was completely shut off, with only the Si target turned on and the sputtering power set to 350 W, depositing a 20 nm thick 100% pure Si film. After stripping off the excess resist, a radial gradient intermediate layer with a constant total thickness of 20 nm was formed on the GaN surface, but with the phase composition ratio gradually changing from the center to the periphery in a multi-level stepwise manner.
[0066] The third step is to remove the natural oxides in the intermediate layer: A GaN epitaxial wafer with a radially varying compositional gradient intermediate layer was placed in a dilute hydrofluoric acid cleaning solution at room temperature. This cleaning solution was prepared by diluting 50% concentrated hydrofluoric acid with deionized water at a volume ratio of 1:20. The GaN epitaxial wafer was completely immersed in the dilute acid solution and allowed to stand for 2–5 minutes to allow the dilute hydrofluoric acid to thoroughly dissolve the natural oxide layer and surface impurities, while ensuring that the intrinsic morphology of the material is not damaged.
[0067] After chemical treatment, the single-crystal diamond and GaN epitaxial wafer are quickly transferred to an ultrapure water bath and continuously rinsed for 6-8 minutes at a flow rate of 8-10 L / min. After rinsing, they are transferred to a high-vacuum spin dryer and spun dry at a high speed of 3000-3500 rpm for 2-3 minutes under a 60 °C environment with 99.9% pure hot nitrogen gas.
[0068] Step 4: Ultra-high vacuum surface activation and room temperature bonding: After spin drying, the GaN epitaxial wafer with a gradient radially varying intermediate layer and the single-crystal diamond are simultaneously fed into an ultra-high vacuum surface activation bonding chamber. The chamber's base vacuum is then evacuated to 5.0 × 10⁻⁶. -7 At Pa, a high-energy Ar atomic beam was used to simultaneously bombard the interlayer and the surface of the single-crystal diamond to be bonded for 1 min, with the beam energy set to 1.0~1.5 keV and the ion beam current density set to 30~50 μA / cm. 2Immediately after bombardment, the beam is shut off. While maintaining room temperature in the cavity, the GaN epitaxial wafer is precisely aligned and bonded to the activated surface of the single-crystal diamond, and a uniformly distributed axial mechanical pressure of 2.0 MPa is directly applied. This mechanical pressure is maintained for 10–15 minutes to achieve final bonding.
[0069] Step 5, removal of the original substrate: A laser lift-off process was used to safely peel off and remove the original sapphire growth substrate from the bonded heterostructure, ultimately obtaining a high-quality target GaN / diamond heterostructure integrated wafer.
[0070] Step 6, Bonding quality inspection: The cleaned GaN / diamond integrated wafer was dried with high-purity argon gas and placed under a scanning acoustic microscope for non-destructive testing of the void ratio at the bonding interface. The test results show that the GaN / diamond integrated wafer prepared in this embodiment has an interface void ratio of only 8.58% (test results are shown in the figure). Figure 7 (As shown).
[0071] Comparative Example 1 This comparative example provides a GaN / diamond bonding structure using 3C-SiC as a homogeneous intermediate layer alone and its preparation method, as detailed below: Step 1, ultra-clean sample pretreatment: A sapphire-based GaN epitaxial wafer (surface roughness Ra < 5 nm) and a single-crystal diamond substrate of the same size (surface roughness Ra < 10 nm) are provided. The GaN epitaxial wafer and the single-crystal diamond are sequentially immersed in high-purity acetone, high-purity anhydrous ethanol, and deionized water, and each is continuously ultrasonically cleaned for 8 min at room temperature to remove trace amounts of organic residues and foreign particles adsorbed on the surface. Then, the surface of the GaN epitaxial wafer is completely dried using a high-purity nitrogen gas flow.
[0072] The single-crystal diamond was immersed in a pre-prepared alkaline cleaning solution. This alkaline solution was prepared by mixing 10% (w / w) high-purity NaOH solution, 30% (w / w) H2O2, and deionized water in a volume ratio of 1:1:4. The solution was heated to 65 °C and continuously immersed for 10–15 min.
[0073] The second step is the deposition of the intermediate layer: The dried GaN epitaxial wafer was placed into the ultra-high vacuum deposition chamber of a multi-target magnetron sputtering system. The base vacuum level of the deposition chamber was evacuated to 2.0 × 10⁻⁶. -5 High-purity argon gas was introduced at a flow rate of 20–40 sccm, and the working pressure was maintained at 0.5 Pa. Then, the radio frequency assisted ion beam source was turned on, and the ion bombardment energy was set to 1–2 keV, with an ion beam current density of 50–80 μA / cm. 2The surface of the GaN epitaxial wafer was continuously bombarded for 3–6 min to remove the natural oxide layer and induce the exposure of unsaturated dangling bonds in the surface lattice, thus completing surface activation. Subsequently, the 3C-SiC target was turned on, and the sputtering power was set to 400 W to deposit a homogeneous 3C-SiC film with a thickness of approximately 20 nm in the intermediate layer.
[0074] The third step is to remove the natural oxides in the intermediate layer: The GaN epitaxial wafer with a 3C-SiC interlayer was placed in a dilute hydrofluoric acid cleaning solution at room temperature. This cleaning solution was prepared by diluting 50% concentrated hydrofluoric acid with deionized water at a volume ratio of 1:20. The GaN epitaxial wafer was completely immersed in the dilute acid solution and allowed to stand for 2–5 minutes to allow the dilute hydrofluoric acid to thoroughly dissolve the natural oxide layer and surface impurities, while ensuring that the intrinsic morphology of the material is not damaged.
[0075] After chemical treatment, the single-crystal diamond and GaN epitaxial wafer are quickly transferred to an ultrapure water bath and continuously rinsed for 6-8 minutes at a flow rate of 8-10 L / min. After rinsing, they are transferred to a high-vacuum spin dryer and spun dry at a high speed of 3000-3500 rpm for 2-3 minutes under a 60 °C environment with 99.9% pure hot nitrogen gas.
[0076] Step 4: Ultra-high vacuum surface activation and room temperature bonding: After spin drying, the GaN epitaxial wafer with the 3C-SiC interlayer and the single-crystal diamond are simultaneously placed into an ultra-high vacuum surface activation bonding chamber. The chamber's base vacuum is then evacuated to 5.0 × 10⁻⁶. -7 At Pa, a high-energy Ar atomic beam was used to simultaneously bombard the interlayer and the surface of the single-crystal diamond to be bonded for 1 min, with the beam energy set to 1.0~1.5 keV and the ion beam current density set to 30~50 μA / cm. 2 Immediately after the bombardment, the beam was shut off. While maintaining the cavity at room temperature, the GaN epitaxial wafer was precisely aligned and bonded to the activated single-crystal diamond surface, and a uniformly distributed axial mechanical pressure of 2.0 MPa was directly applied. This mechanical pressure was maintained for 10–15 minutes, ultimately achieving bonding.
[0077] Step 5, removal of the original substrate: The original sapphire growth substrate was peeled off and removed from the bonded heterostructure using a laser lift-off process, ultimately obtaining the target GaN / diamond heterostructure integrated wafer.
[0078] Step 6: Bonding quality inspection The cleaned GaN / diamond integrated wafer was dried with high-purity argon gas and placed under a scanning acoustic microscope for non-destructive testing of the void ratio at the bonding interface. The test results showed that the interface void ratio of the GaN / diamond integrated wafer prepared in this comparative example was 25.70%. Figure 8 As shown.
[0079] Comparative Example 2 This comparative example provides a GaN / diamond bonded structure using 4H-SiC as a homogeneous intermediate layer and its preparation method, as detailed below: Step 1, ultra-clean sample pretreatment: A sapphire-based GaN epitaxial wafer (surface roughness Ra < 5 nm) and a single-crystal diamond substrate of the same size (surface roughness Ra < 10 nm) are provided. The GaN epitaxial wafer and the single-crystal diamond are sequentially immersed in high-purity acetone, high-purity anhydrous ethanol, and deionized water, and each is continuously ultrasonically cleaned for 8 min at room temperature to remove trace amounts of organic residues and foreign particles adsorbed on the surface. Then, the surface of the GaN epitaxial wafer is completely dried using a high-purity nitrogen gas flow.
[0080] The single-crystal diamond was immersed in a prepared alkaline solution. This alkaline solution was made by mixing 30% ammonia, 30% H₂O₂, and deionized water in a volume ratio of 1:1:5. The solution was heated to 60 °C and immersed continuously for 10-15 minutes.
[0081] The second step is the deposition of the intermediate layer: The dried GaN epitaxial wafer was placed into the ultra-high vacuum deposition chamber of a multi-target magnetron sputtering system. The base vacuum level of the deposition chamber was evacuated to 3.0 × 10⁻⁶. -5 High-purity argon gas was introduced at a flow rate of 30-50 sccm, and the working pressure was maintained at 0.5 Pa. Then, the radio frequency assisted ion beam source was turned on, and the ion bombardment energy was set to 1-2 keV, with an ion beam current density of 40-60 μA / cm. 2 The surface of the GaN epitaxial wafer was continuously bombarded for 3-5 minutes to remove the natural oxide layer and induce the exposure of unsaturated dangling bonds in the surface lattice, thus completing surface activation. Subsequently, the 4H-SiC target was turned on, and the sputtering power was set to 400 W to deposit a 4H-SiC film with a thickness of about 20 nm in the intermediate layer.
[0082] The third step is to remove the natural oxides in the intermediate layer: The GaN epitaxial wafer with the intermediate layer was placed in a dilute hydrochloric acid cleaning solution at room temperature. This solution was prepared by diluting 37% hydrochloric acid with deionized water at a volume ratio of 1:5. The wafer was completely immersed in this solution and allowed to stand for 15-20 minutes. The dilute hydrochloric acid dissolves the natural oxide layer and surface impurities without damaging the intrinsic morphology.
[0083] After soaking, the GaN epitaxial wafer and single-crystal diamond were quickly transferred to a water bath and rinsed for 6-8 minutes at a flow rate of 8-10 L / min. They were then transferred to a high-vacuum spin dryer and dried under 65°C air. ° C. In an environment of hot high-purity nitrogen with a purity of 99.9%, spin dry at a high speed of 3000-3500 rpm for 2-3 minutes.
[0084] Step 4: Ultra-high vacuum surface activation and room temperature bonding: After spin drying, the GaN epitaxial wafer with a 4H-SiC interlayer and the single-crystal diamond are simultaneously placed into an ultra-high vacuum surface activation bonding chamber. The chamber's base vacuum is then evacuated to 5.0 × 10⁻⁶. -7 At Pa, a high-energy Ar atomic beam was used to simultaneously bombard the interlayer and the surface of the single-crystal diamond to be bonded for 1 min, with the beam energy set to 1.0~1.5 keV and the ion beam current density set to 30~50 μA / cm. 2 Immediately after the bombardment, the beam was shut off. While maintaining the cavity at room temperature, the GaN epitaxial wafer was precisely aligned and bonded to the activated single-crystal diamond surface, and a uniformly distributed axial mechanical pressure of 2.0 MPa was directly applied. This mechanical pressure was maintained for 10–15 minutes, ultimately achieving bonding.
[0085] Step 5, removal of the original substrate: The original sapphire growth substrate was peeled off and removed from the bonded heterostructure using a laser lift-off process, ultimately obtaining the target GaN / diamond heterostructure integrated wafer.
[0086] Step 6, Bonding quality inspection: The cleaned GaN / diamond integrated wafer was dried with high-purity argon gas and placed under a scanning acoustic microscope for non-destructive testing of the void ratio at the bonding interface. The test results showed that the interface void ratio of the GaN / diamond integrated wafer prepared in this comparative example was 42.69%. Figure 9 As shown.
[0087] Compared to the comparative sample 1, which only used 3C-SiC as the coating layer (its porosity was as high as 25.70%), Figure 8 As shown), the interface void ratio of the sample in Example 1 of this invention is only 8.32%; compared with the sample in Comparative Example 2, which uses only 4H-SiC as the coating layer (its void ratio is as high as 42.69%), the void ratio of the sample in Example 1 is only 8.32%. Figure 9 As shown in the figure, the interface void ratio of the sample in Example 2 of the present invention is only 8.58%. This indicates that the coating layer with radially varying step-type composition gradient of the present invention can significantly reduce the unbonded void ratio between gallium nitride and diamond, and avoid contact failure between gallium nitride and diamond.
[0088] The above embodiments merely illustrate several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this patent should be determined by the appended claims.
Claims
1. A coated gallium nitride substrate, characterized in that, The system includes a GaN epitaxial wafer and a coating layer deposited on the GaN epitaxial wafer. The phase composition of the coating layer is distributed in a stepped gradient along the radial direction. The phase composition at the center of the coating layer is pure SiC, the phase composition at the outermost edge of the coating layer is pure Si, and the phase composition in the transition region between the center and the outermost edge of the coating layer is a mixed phase of SiC and Si. From the center to the outermost edge, the proportion of Si in the transition region increases stepwise.
2. The gallium nitride substrate with coating as described in claim 1, characterized in that, The initial surface roughness Ra of the GaN epitaxial wafer is less than 5 nm; and / or, The phase composition at the center of the coating layer is pure 3C-SiC, 4H-SiC, or 6H-SiC; and / or, The thickness of the coating layer is 10~30 nm; and / or, The original substrate of the GaN epitaxial wafer is sapphire.
3. A gallium nitride / diamond bonding structure, characterized in that, It includes the coated gallium nitride substrate as described in claim 1 or 2 and a single crystal diamond, wherein the single crystal diamond is bonded to the coating layer.
4. The gallium nitride / diamond bonding structure as described in claim 3, characterized in that, The initial surface roughness Ra of the single-crystal diamond is less than 10 nm.
5. A method for preparing a coated gallium nitride substrate as described in claim 1 or 2, characterized in that, Includes the following steps: (1) The GaN epitaxial wafer is subjected to ultra-clean cleaning pretreatment to remove surface impurities; (2) A coating layer is deposited on the surface of the pretreated GaN epitaxial wafer using photolithography and patterning overlay processes to obtain the coated gallium nitride substrate. The phase composition ratio of the coating layer is distributed in a stepped gradient along the radial direction. The phase composition at the center of the coating layer is pure SiC, the phase composition at the outermost edge of the coating layer is pure Si, and the phase composition in the transition region between the center of the coating layer and the outermost edge of the coating layer is a mixed phase of SiC and Si. From the center to the outermost edge, the proportion of Si in the transition region increases stepwise.
6. A method for preparing the gallium nitride / diamond bonding structure as described in claim 3 or 4, characterized in that, Includes the following steps: (1) Perform ultra-clean cleaning pretreatment on single crystal diamond and GaN epitaxial wafers to remove surface impurities; (2) A coating layer is deposited on the surface of the pretreated GaN epitaxial wafer using photolithography and patterning overlay processes. The phase composition ratio of the coating layer is distributed in a stepped gradient along the radial direction. The phase composition at the center of the coating layer is pure SiC, the phase composition at the outermost edge of the coating layer is pure Si, and the phase composition of the transition region between the center of the coating layer and the outermost edge of the coating layer is a mixed phase of SiC and Si. From the center to the outermost edge, the proportion of Si in the transition region increases stepwise. (3) The GaN epitaxial wafer after the deposition of the coating layer is chemically cleaned and dried to remove the natural oxide layer and surface impurities; (4) The pretreated single crystal diamond and the bonding surface of the coating layer are activated, and then directly bonded to obtain the gallium nitride / diamond bonding structure.
7. The method for preparing the gallium nitride / diamond bonding structure as described in claim 6, characterized in that, It also includes step (5): peeling off the original substrate of the GaN epitaxial wafer.
8. The method for preparing a coated gallium nitride substrate as described in claim 5, characterized in that, The coating layer is deposited using a multi-target co-sputtering system with a first cathode target and a second cathode target. The first cathode target is equipped with a SiC target, and the second cathode target is equipped with a Si target.
9. The method for preparing the gallium nitride / diamond bonding structure as described in claim 6, characterized in that, In step (4), the activation process is as follows: under ultra-high vacuum conditions, the surface to be bonded is bombarded using a fast atom beam or a plasma beam, wherein the ultra-high vacuum pressure reaches 10... -7 Pa level.
10. The method for preparing the gallium nitride / diamond bonding structure as described in claim 6, characterized in that, In step (3), the chemical cleaning uses hydrofluoric acid cleaning solution, or a mixture of hydrochloric acid and hydrogen peroxide cleaning solution; and / or, In step (1), the pretreatment is as follows: the single crystal diamond and the GaN epitaxial wafer are first subjected to multi-stage ultrasonic cleaning using acetone, anhydrous ethanol and deionized water in sequence. The single-crystal diamond is then cleaned with an alkaline solution, which is a mixture of ammonia and hydrogen peroxide, or a mixture of sodium hydroxide and hydrogen peroxide.